ANALISA PENGARUH GRID RASIO DAN FAKTOR EKSPOSI TERHADAP GAMBARAN RADIOGRAFI PHANTOM THORAX - Aulia Narindra Mukhtar; Heri Sutanto (Youngster Physics Journal, 2015)
Analysis of the influence of the grid has been determined and the ratio of the radiographic expose factor thorax phantom with grid ratio and expose factor variation to analyze the density and contrast on chest radiographs. Research methods using phantom anthoropomorphic, densitometer and X-ray equipments. Irradiation conditions are given with some expose factor variation is 55 kV 16 mAs, 65 kV 8 mAs, 75 kV 3.2 mAs, and a variety of grid ratio 6:1 and 8:1. Research data is processed and made in the form of a graph of the density of the contrast of the grid ratio and expose factor variation. The higher the ratio of the grid will cause a decrease in the density of radiographs, but does not always lead to increasing or decreasing the contrast radiographs. Results overview on to 5 thorax phantom organ that produces the highest optical density in the use of expose factors 65 kV, 8 mAs on both the grid ratio.Keywords: Grid ratio, expose factor, radiographs